Innovative Approaches to Teaching Philosophy through Media and Multimedia Tools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the importance of innovative approaches in the process of teaching philosophy using media and multimedia tools. In the modern era of information technology, it is necessary to modernize the educational process. It is important for teachers teaching with the help of media and multimedia tools to organize the educational process in a new way, to create an opportunity to develop students' analysis, logical thinking and creative approach to problems. The article highlights the role of modern pedagogical technologies, including virtual reality, animation, infographics, audio and video materials, in teaching philosophy. It also presents the results of a series of experiments on the influence of multimedia on increasing student motivation, ensuring the effectiveness of communication in education and the acquisition of philosophical knowledge. The possibilities of effective use of collaborative learning, online resources and interactive platforms will be highlighted. Based on this, recommendations are developed to improve the effectiveness of using modern technologies in teaching philosophy.